Foreign to whom? Constraining the moral foreign language effect on bilinguals' language experience. (27th December 2022) - Del Maschio, Nicola; Del Mauro, Gianpaolo; Bellini, Camilla; Abutalebi, Jubin; Sulpizio, Simone
Abstract: The moral foreign language effect (MFLE) describes how people's decisions may change when a moral dilemma is presented in either their native (NL) or foreign language (FL). Growing attention is being directed to unpacking what aspects of bilingualism may influence the MFLE, though with mixed or inconclusive results. The current study aims to bridge this gap by adopting a conceptualization of bilingualism that frames this construct as a composite and continuous measure. In a between-group analysis, we asked 196 Italian–English bilinguals to perform a moral dilemmas task in either their NL (i.e., Italian) or FL (i.e., English). In a within-group analysis, we evaluated the effects of FL age of acquisition, FL proficiency, and language dominance – all measured as continuous variables – on moral decision-making. Overall, findings indicate that differences within bilinguals' language experience impact moral decisions in an FL. However, the effect of the linguistic factors considered was not ubiquitous across dilemmas, and not always emerged into a MFLE. In light of these results, our study addresses the importance of treating bilingualism as multidimensional, rather than a unitary variable. It also discusses the need to reconceptualize the FLE and its implications on moral decision-making.